(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
Background. Turf toe is used to describe an injury occurring at the plantar aspect of the metatarsophalangealsesamoid complex of the hallux. Typically seen in athletes, it occurs due to hyperdorsiﬂexion and axial loading of the hallux metatarsophalangeal joint with the foot fxed in equinus. The injury causes pain and joint instability, missed athletic activity and potentially end careers. Turf toe can be managed conservatively or operatively, with controversy regarding the indications for operative intervention. This study aims to conduct a systematic review to determine whether and in what circumstances operative intervention is superior to conservative management of turf toe in adults. Methods. A systematic review of the literature was performed using PubMed, Embase, Cochrane and Scopus databases. The search terms used were “turf toe”, “frst metatarsophalangeal joint injury”, “conservative”, “nonoperative”, and “operative”. All articles published in English reporting on the management of turf toe were reviewed. The primary outcome measure was the time to return to pre-injury activity with the secondary outcome of the time to symptom resolution. Results. Seven studies met the inclusion criteria. Three patients were successfully managed conservatively returning to athletic activity, on average at 12 weeks. Seventeen patients underwent surgical intervention with an average return to athletic activity at 18 weeks. Conclusion. Operative intervention was shown to give a successful outcome in patients with grade three turf toe injuries or those who have failed conservative management. However, there is insufcient evidence to determine whether operative intervention is superior to conservative management. Keywords: turf toe, frst metatarsophalangeal joint injury, conservative, nonoperative, and operative.